The impact of biomass consumption on CO2 emissions An empirical investigation from Turkey - Katircioglu, Salih Turan (Emerald Group Publishing Ltd, 2015)
Purpose - The purpose of this study is to investigate the long-term equilibrium relationship between carbon dioxide (CO2) emissions and total biomass consumption (BC) in Turkey, which has a rich diversity of ecological conditions prevailing throughout its regions. Design/methodology/approach - Bounds tests and conditional error correction models under the autoregressive distributed lag approach have been applied to annual data that cover the 1980-2010 period. Findings - Results suggest that CO2 emissions are in a long-term equilibrium relationship with total BC in Turkey. BC has a negative effect on CO2 emissions; 1 per cent increase in total BC would lead to 0.029 per cent reduction in CO2 emissions. Long-term coefficient of fossil fuel consumption for CO2 emissions is positive and elastic, 1.247. Finally, conditional error correction model of the present study reveals that CO2 emission in Turkey converges to its economic long-term equilibrium very quickly by 93.7 per cent speed of adjustment through the channel of BC and fossil fuel consumption. Originality/value - Although there have been a considerable number of studies investigating the link between total energy consumption and CO2 emissions in the literature, searching the contribution of components of energy to CO2 emissions deserves attention. Therefore, this study contributes to the literature by investigating the effect of BC on CO2 emissions in the case of Turkey.
Keywords: Turkey; CO2 emissions; Biomass consumption; Environmental pollution; Fuel consumption